Mechanical Calculation of Flexible Wires of Overhead Lines with Aerial Barrage Balls in Different Climatic Regimes - Yu. V. Bladyko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2019)
Climatic conditions and loads on wires and cables of overhead lines are calculated in accordance with the Technical Code of the Established Practice of TCP 339–2011 and the seventh edition of Electrical Installation Rules. Aviation aerial barrage balls are considered as concentrated loads acting on the wire. The article deals with the mechanical calculation of flexible wires of overhead lines, in which barrage balls warning spheres are installed. The formulas for determining the sag are given for a different number of barrage balls as a function of their number and the coefficient of concentrated forces. This takes into account the difference in suspension heights, tension insulators strings, wind and ice loads. Equations of state are obtained that took into account the weight and wind loads on the wire, as well as the load factors in two planes, depending on the number of barrage balls. Calculations of sag and tension for different span loads have been performed. With the action of wind and ice loads, the tensions and sags increase, in the ice regime the tension has exceeded the permissible value. The case of the appearance of an additional concentrated load in the span is considered.